Detection and Analysis of Man-Machine Interactive Software Vulnerabilities Based on Ultrasonic Data Acquisition and Signal Processing Algorithms - Lei Zhao (Advances in Multimedia)
With the gradual increase in the informatization, there is much software in various industries, such as data management, business execution, public orientation, and company OA, which greatly facilitates the development of various tasks, but it also brings many hidden dangers. There exist certain vulnerabilities in some software, which have become backdoors to be attacked. In view of these needs and potential hazards, the ultrasonic data acquisition and signal processing algorithms are introduced in this paper, analyzing and grasping the possibility of potentially dangerous paths by combining the instruction addresses and locations of software vulnerabilities, and avoid the existence of these software vulnerabilities through corresponding constraint instructions. The simulation experiment results prove that the ultrasonic data acquisition and signal processing algorithms are effective and can support the detection and analysis of man-machine interactive software vulnerabilities.